Using Ethnography to Identify Barriers and Facilitators to Optimal Infant and Young Child Feeding in Rural Ghana: Implications for Programs - Armar-Klemesu, M.; Osei-Menya, S.; Zakariah-Akoto, S.; Tumilowicz, A.; Lee, J.; Hotz, C. (SAGE Publications Inc., 2018)
Background: Understanding the context of infant and young child feeding (IYCF) is recognized as essential for designing appropriate complementary feeding interventions. Objective: Our objective was to study household IYCF behaviors in 2 districts in southern and northern Ghana to identify opportunities to improve existing nutrition programs. Methods: We interviewed 80 caregivers of children aged 6 to 23 months using ethnographic methods, including free listing, guided discussions and cognitive mapping techniques, and 24-hour dietary recall. Descriptive statistics and thematic content analysis were used to analyze quantitative and qualitative data. Results: In both settings, children’s diets were predominantly maize based. Fish, the main animal source food, was consumed daily but in very small quantities. Milk was consumed by only a few children, in tea and porridge. Fruits were seldom consumed. Household food production did not meet requirements, and the markets were heavily relied on for staples and other key ingredients. Most caregivers demonstrated basic knowledge and understanding of key health and nutrition concepts. Barriers to optimal child feeding identified were lack of money to purchase the nutritious foods recommended for children, seasonal food insecurity, and some caregiver beliefs, practices, and nutrition knowledge gaps. Positive contextual features include caregiver recognition of the dietary needs of young children and commitment to provide foods to meet these needs. Conclusion: Our findings suggest that complementary feeding in these rural settings can be improved through reinforcement or modification of strategic components of local health and nutrition education in light of existing barriers and enablers to optimal IYCF. © 2018, © The Author(s) 2018.
Keywords: Ethnography; Ghana; Infant and young child feeding; Nutrition interventions